2011
DOI: 10.1021/jf201836g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Approach for Simultaneous Estimation of Multiple Health-Promoting Effects of Foods

Abstract: The investigation of new food constituents for purposes of disease prevention or health promotion is an area of increasing interest in food science. This paper proposes a new system that allows for simultaneous estimation of the multiple health-promoting effects of food constituents using informatics. The model utilizes expression data of intracellular marker proteins as descriptors that reply to stimulation of a constituent. To estimate three health-promoting effects, namely, cancer cell growth suppression ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Analysis of the chemical constituents by Matsuo et al has revealed that the most abundant polyphenols in rabbiteye BBL are oligomeric proanthocyanidins (Matsuo, et al, 2010). Since they can suppress hepatitis C virus replication (Nagahama, et al, 2011;Takeshita, et al, 2009), BBL have recently come to be used as a tea also in both North America and Japan. Recent studies show that the proanthocyanidins from rabbiteye BBL exert not only suppressive effect on hepatitis C virus replication but also some health-promoting effects in vitro or in vivo (Inoue, et al, 2011;Nagahama, et al, 2011;Takami, et al, 2010;Takeshita, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the chemical constituents by Matsuo et al has revealed that the most abundant polyphenols in rabbiteye BBL are oligomeric proanthocyanidins (Matsuo, et al, 2010). Since they can suppress hepatitis C virus replication (Nagahama, et al, 2011;Takeshita, et al, 2009), BBL have recently come to be used as a tea also in both North America and Japan. Recent studies show that the proanthocyanidins from rabbiteye BBL exert not only suppressive effect on hepatitis C virus replication but also some health-promoting effects in vitro or in vivo (Inoue, et al, 2011;Nagahama, et al, 2011;Takami, et al, 2010;Takeshita, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Since they can suppress hepatitis C virus replication (Nagahama, et al, 2011;Takeshita, et al, 2009), BBL have recently come to be used as a tea also in both North America and Japan. Recent studies show that the proanthocyanidins from rabbiteye BBL exert not only suppressive effect on hepatitis C virus replication but also some health-promoting effects in vitro or in vivo (Inoue, et al, 2011;Nagahama, et al, 2011;Takami, et al, 2010;Takeshita, et al, 2009). Noteworthy, orally administered proanthocyanidins fraction from rabbiteye BBL, which is separated by a similar method as our study, enhances lipolysis in the liver, resulting in the fraction exerts hypolipidemic effect on obese Otsuka Long-Evans Tokushima Fatty rats (Inoue, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%